2022
DOI: 10.1007/s00253-022-11965-4
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression a novel fibronectin—collage fusion peptide modulating stem cell stemness via integrin β3

Abstract: Constructing bionic extracellular matrix (ECM) is an attractive proposition for tissue engineering and clinical regeneration therapy involving the stemness of stem cells. Here, a novel recombinant protein fibronectin-collagen peptide (FCP) was designed to modulate the function of ECM expressed by Picha. pastoris strain X33. This FCP promotes cell migration and adhesion and maintains rBMSC stemness by binding integrin β3. Its effects were blocked by both integrin β3 siRNA and the integrin β3 inhibitor Cilengiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…After obtaining high-purity 0630 protein, the characterization of the secondary structure of 0630 protein in solution was carried out by CD spectroscopy, which evaluates the secondary structure by using the differential absorption of left- and right-handed circularly polarized light in asymmetric environments . The results were obtained with a very pronounced negative absorption peak at 198 nm, but a small and broad positive absorption peak at 250–300 nm This may be due to the presence of irregular coil structures in the protein secondary structure, suggesting that the spectral characteristics of the 0630 protein are similar to those of typical denatured collagen. , These results suggest that the 0630 structure is predominantly random coils.…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining high-purity 0630 protein, the characterization of the secondary structure of 0630 protein in solution was carried out by CD spectroscopy, which evaluates the secondary structure by using the differential absorption of left- and right-handed circularly polarized light in asymmetric environments . The results were obtained with a very pronounced negative absorption peak at 198 nm, but a small and broad positive absorption peak at 250–300 nm This may be due to the presence of irregular coil structures in the protein secondary structure, suggesting that the spectral characteristics of the 0630 protein are similar to those of typical denatured collagen. , These results suggest that the 0630 structure is predominantly random coils.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that fibronectin can be subdivided into plasma fibronectin and cellular fibronectin, the former one is always synthesized by hepatocytes and the latter one is produced by a variety of cells, such as chondrocytes and so on [ 14 ]. Furthermore, fibronectin is well-documented for its function in several biological procedures containing cell adhesion, migration, stemness, differentiation and angiogenesis [ 15 18 ]. A lot of studies have indicated that cell adhesion to extracellular fibronectin played a key role in tumorigenesis[ 19 ], and malignant progression in multiple cancer types, such as the development of the resistance to anoikis and chemotherapy [ 20 , 21 ], cancer metastasis [ 22 ], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Sana et al used RGD and fibronectin-immobilized chitosan scaffolds to piggyback human dental pulp stem cells (hDPSCs) and found the scaffolds can significantly promote cell migration, proliferation, and differentiation [20]. Our team [21] combined FNIII10 and CC (human collagen-like protein) proteins to obtain FCP. The ECM-mimetic FCP provides a microenvironment that supports stem cell localization, proliferation, differentiation, and stemness maintenance.…”
Section: Introductionmentioning
confidence: 99%